The Earliest Residential Area Planning Based on the Neighbourhood Unit Concept in Postwar Japan - Kim, Joonyoung; Nakano, Shigeo (International Planning History Society Proceedings, 2024)
The neighbourhood unit concept, proposed in the USA in 1923, was applied in city planning across the world. In Japan, it was introduced in the late 1930s, and current urban planning also uses neighbourhood unit concept as a basic theory for residential area planning. However, the advanced practice of neighbourhood unit concept, which was attempted immediately after the World War II, has not been clarified. This paper clarifies what experiments were made between standardisation studies from before the end of the war and the large-scale application of neighbourhood unit, represented by the Senri New Town development after 1960. three planning proposals were published in journals in the late 1940s and 1950s for actual suburban areas of Japanese metropolises. All were proposed by urban planners and architects, and each had a diverse and highly planned level of spatial design that reflected their own ideas. When collated against the six principles of the neighbourhood unit concept, a certain trend of principles that were faithfully followed and those that were not was apparent. The above has revealed a part of the advanced practice of the neighbourhood unit concept in post-war Japan.